The Effect of Organizational Culture, Work Environment and Satisfaction On Motivation and Job Promotion - Sudarmo Sudarmo; M Hatta; Saiful Anwar (Relevance: Journal of Management and Business, 2020)
This study was conducted due to differences in the study results, Julianto, Romi Haryo dan Hendriani, Susi (2014) and Afifah et al., (2017) show that satisfaction effect to the motivation, in other hand Faysica et al., (2016) put forward different results. This study aims to re-examine satisfaction with adding variable: work environment and job satisfaction with two Y variable (motivating and promotion) at PT. Altrak 1978 Balikpapan. The sampling technique used a questionnaire that is a sample of 93 respondents, random sampling and The data were analyzed using used multiple regression analysis with SPSS 21. The results of multiple regression test 1, that work culture, work environment and job satisfaction significantly influence employee work motivation. The results of multiple regression test 2, the organizational culture, work environment and job satisfaction are significant to the promotion of position and job satisfaction is significant to the promotion of position.